Use Of Anti-Epileptics For Seizure Prophylaxis After Traumatic Brain Injury In The Pediatric Population - Aroosh Khan; Sidra Tul Muntaha; Hammad Ayaz; Afrah Tariq; Huma Mughal (Journal of Rawalpindi Medical College)
Objective: To determine the frequency of Early Post-Traumatic Seizures (EPTS) in patients receiving anti-epileptic prophylaxis after moderate to severe traumatic brain injury (TBI) in children.